Association Between Dietary Habits in Midlife With Dementia Incidence Over a 20-Year Period. (3rd January 2023) - Glans, Isabelle; Sonestedt, Emily; Nägga, Katarina; Gustavsson, Anna-Märta; González-Padilla, Esther; Borne, Yan; Stomrud, Erik; Melander, Olle; Nilsson, Peter M.; Palmqvist, Sebastian; Hansson, Oskar
Abstract : Background and Objectives: Dementia cases are expected to triple during the next 30 years, highlighting the importance of finding modifiable risk factors for dementia. The aim of this study was to investigate whether adherence to conventional dietary recommendations or to a modified Mediterranean diet are associated with a subsequent lower risk of developing all-cause dementia, Alzheimer disease (AD), vascular dementia (VaD), or with future accumulation of AD-related β-amyloid (Aβ) pathology. Methods: Baseline examination in the prospective Swedish population-based Malmö Diet and Cancer Study took place in 1991–1996 with a follow-up for incident dementia until 2014. Nondemented individuals born 1923–1950 and living in Malmö were invited to participate. Thirty thousand four hundred forty-six were recruited (41% of all eligible). Twenty-eight thousand twenty-five had dietary data and were included in this study. Dietary habits were assessed with a 7-day food diary, detailed food frequency questionnaire, and 1-hour interview. Main outcomes were incident all-cause dementia, AD, or VaD determined by memory clinic physicians. Secondary outcome was Aβ-accumulation measured using CSF Aβ42 (n = 738). Cox proportional hazard models were used to examine associations between diet and risk of developing dementia (adjusted for demographics, comorbidities, smoking, physical activity, and alcohol). Results: Sixty-one percent were women, and the mean (SD) age was 58.1 (7.6) years. One thousand nine hundred forty-three (6.9%) were diagnosed with dementia (median follow-up, 19.8 years). Individuals adhering to conventional dietary recommendations did not have lower risk of developing all-cause dementia (hazard ratio [HR] comparing worst with best adherence, 0.93, 95% CI 0.81–1.08), AD (HR 1.03, 0.85–1.23), or VaD (HR 0.93, 0.69–1.26). Neither did adherence to the modified Mediterranean diet lower the risk of developing all-cause dementia (HR 0.93 0.75–1.15), AD (HR 0.90, 0.68–1.19), or VaD (HR 1.00, 0.65–1.55). The results were similar when excluding participants developing dementia within 5 years or those with diabetes. No significant associations were found between diet and abnormal Aβ accumulation, conventional recommendations (OR 1.28, 0.74–2.24) or modified Mediterranean diet (OR 0.85, 0.39–1.84). Discussion: In this 20-year follow-up study, neither adherence to conventional dietary recommendations nor to modified Mediterranean diet were significantly associated with subsequent reduced risk for developing all-cause dementia, AD dementia, VaD, or AD pathology.